Konflik Teori Belajar dalam Pola Belajar Siswa Digital Native - Ahmar, Dewi Satria; Azzajjad, Muhammad Fath (CV. AKIRA JAVA BULU, 2025)
Students' learning habits have changed dramatically due to the rapid development of digital technology, especially among digital natives. However, many teachers still rely on traditional learning theories such as behaviorism and cognitivism, resulting in a disconnect between instructional approaches and students’ learning preferences. This study explores the conflict between established learning theories and the actual learning behaviors of digital native students in secondary schools in Palu City, Indonesia. Using a qualitative descriptive method, data were collected through in-depth interviews with five teachers and seven students, alongside classroom observations and documentation. Thematic coding analysis revealed a significant pedagogical gap: while students prefer interactive, technology-driven, and self-directed learning experiences, most teachers continue to use one-way, teacher-centered instructional methods. This mismatch limits student engagement and reduces the overall effectiveness of the learning process. The findings suggest that current pedagogical strategies fail to align with the characteristics and expectations of digital native learners. The study concludes that to address this challenge, educators must shift toward constructivist and connectivist approaches that integrate digital tools and platforms. A reflective transformation in teaching practices is urgently needed to bridge the gap between theoretical frameworks and the practical demands of learning in the digital age.